Business Analytics and Market Adaptation in the E-Commerce Industry in Nigeria - Daodu, Ladi; Bhaumik, Amiya; Morakinyo, Akinola (Acta Universitatis Danubius. Œconomica, 2022)
The study examined the impact of business analytics on market adaptation in the eCommerce industry in Nigeria. Using purposive sampling and random sampling techniques, a sample of 40 respondents from various eCommerce organizations was taken. The data collected were analyzed using the quantitative approach. Precisely, both correlation and ordinal regression analyses were applied. The result from the study shows that the most important aspect of business analytics that can have a significant impact on market adaptation is the area of data analysis and application of the result to decision-making in the organization. The study recommends the application of business analytics to eCommerce businesses if they want to improve their market adaptation.